2006
DOI: 10.1021/bm050868n
|View full text |Cite
|
Sign up to set email alerts
|

Bioinert Surface of Pluronic-Immobilized Flask for Preservation of Hematopoietic Stem Cells

Abstract: The bioinert materials on which cells do not proliferate, differentiate, nor de-differentiate should be useful for the culture and preservation of stem cells. The Pluronic F127, a triblock copolymer of ethylene oxide, and propylene oxide was activated using carbonyldiimidazole (CDI), and CDI-activated Pluronic was subsequently immobilized on the surface of a lysine-coated polystyrene tissue culture flask. The morphology of fibroblasts (L929 cells) on the Pluronic-immobilized flask was spherical, and did not sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Therefore, most cells do not grow on these polymers, which have been used as tissue adhesion barriers. However, it was shown that Pluronics® can be a good substrate for hematopoietic stem cells, supporting their culture and preservation more than conventional tissue culture dishes [57,58]. Recently, the use of Pluronic® F127 (synonymous to poloxamer 407) was reported for tissue engineering applications.…”
Section: Peo/ppo-based Systemsmentioning
confidence: 99%
“…Therefore, most cells do not grow on these polymers, which have been used as tissue adhesion barriers. However, it was shown that Pluronics® can be a good substrate for hematopoietic stem cells, supporting their culture and preservation more than conventional tissue culture dishes [57,58]. Recently, the use of Pluronic® F127 (synonymous to poloxamer 407) was reported for tissue engineering applications.…”
Section: Peo/ppo-based Systemsmentioning
confidence: 99%
“…Also, Pluronic F127 was activated using carbonyldiimidazole and immobilized on the surface of a lysine-coated polystyrene tissue culture flask. 23 In this study, new materials with improved characteristics are prepared by mixing PVA and Pluronic F127 in aqueous solutions and their rheological properties are investigated in order to design thermoresponsive materials with potential biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…albumin, or fibrinogen) on the PEO‐PPO‐PEO surface and did not involve comparison of different single proteins or examine mixed proteins in a complex media. Therefore, although the low biofouling property of PEO‐PPO‐PEO triblock copolymers has been demonstrated previously,22, 24, 25 there is still a lack of complete study of protein adsorption from both single protein solutions and complex media using well‐controlled PEO‐PPO‐PEO surfaces 16, 26…”
Section: Introductionmentioning
confidence: 99%